Lead Transiently Promotes Granulocyte-Macrophage Progenitor Differentiation and Subsequently Suppresses Common Myeloid Progenitor Differentiation. (30th August 2017) - Li, Qian; Zhang, Peng; Yu, Xinchun; Zhao, Yifan; Li, Qiang; Zhang, Yandong; Yang, Zhengli; Xie, Yunli; Xue, Peng; Sun, Shuhui; Jia, Xiaodong; Zhou, Zhijun; et al.
Abstract: Lead (Pb) is a toxic heavy metal affecting human health; it is known to be harmful to various organs or systems, yet the mechanisms by which Pb influences immune cell development remain to be defined. In this study, we show that Pb exposure (1250 ppm via drinking water) selectively impacted the development of myeloid cells (myelopoiesis). After Pb treatment of adult C57BL/6 mice, the numbers of granulocyte-macrophage progenitors (GMP) were consistently reduced, whereas the numbers of myeloid cells were increased at week (wk) 1 and decreased at wk8 after initiating the Pb exposure. Functional assays indicate that Pb accelerated GMP differentiation in a reactive oxygen species-dependent manner after treatment for 1 week and inhibited common myeloid progenitor differentiation by upregulating interferon regulatory factor 8 (IRF8) expression after treatment for 8 weeks. Consistent with the distinct Pb influences on myeloid cells observed at wk1 and wk8, Pb caused an inflammatory environment in vivo at wk8, but not at wk1. Furthermore, like the observations in mice during the Pb exposure, bloods from humans occupationally exposed to Pb had their numbers of monocytes, neutrophils and GMP negatively associated with the Pb concentration, whereas IRF8 expression in common myeloid progenitor, but not GMP, was positively correlated with the Pb concentration. These data suggest an occupationally relevant level of Pb exposure preferentially influences myelopoiesis involving reactive oxygen species and IRF8, which may contribute to the current understanding of the hematopoietic toxicology of Pb.